-7x-6y=5

Add 7x to both sides of the equation.

-6y=5+7x

Divide each term by -6 and simplify.

Divide each term in -6y=5+7x by -6.

-6y-6=5-6+7x-6

Cancel the common factor of -6.

Cancel the common factor.

-6y-6=5-6+7x-6

Divide y by 1.

y=5-6+7x-6

y=5-6+7x-6

Simplify each term.

Move the negative in front of the fraction.

y=-56+7x-6

Move the negative in front of the fraction.

y=-56-7×6

y=-56-7×6

y=-56-7×6

y=-56-7×6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Reorder -56 and -7×6.

y=-7×6-56

Rewrite in slope-intercept form.

y=-76x-56

y=-76x-56

Find the values of m and b using the form y=mx+b.

m=-76

b=-56

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: -76

y-intercept: -56

Slope: -76

y-intercept: -56

Choose 1 to substitute in for x to find the ordered pair.

Replace the variable x with 1 in the expression.

f(1)=-7(1)6-56

Simplify the result.

Multiply 7 by 1.

f(1)=-76-56

Combine the numerators over the common denominator.

f(1)=-7-56

Subtract 5 from -7.

f(1)=-126

Divide -12 by 6.

f(1)=-2

The final answer is -2.

-2

-2

The y value at x=1 is -2.

y=-2

y=-2

Choose 0 to substitute in for x to find the ordered pair.

Replace the variable x with 0 in the expression.

f(0)=-7(0)6-56

Simplify the result.

Simplify each term.

Cancel the common factor of 0 and 6.

Factor 6 out of 7(0).

f(0)=-6(7⋅(0))6-56

Cancel the common factors.

Factor 6 out of 6.

f(0)=-6(7⋅(0))6(1)-56

Cancel the common factor.

f(0)=-6(7⋅(0))6⋅1-56

Rewrite the expression.

f(0)=-7⋅(0)1-56

Divide 7⋅(0) by 1.

f(0)=-(7⋅(0))-56

f(0)=-(7⋅(0))-56

f(0)=-(7⋅(0))-56

Multiply 7 by 0.

f(0)=-0-56

Multiply -1 by 0.

f(0)=0-56

f(0)=0-56

Subtract 56 from 0.

f(0)=-56

The final answer is -56.

-56

-56

The y value at x=0 is -56.

y=-56

y=-56

Create a table of the x and y values.

xy0-561-2

xy0-561-2

Graph the line using the slope and the y-intercept, or the points.

Slope: -76

y-intercept: -56

xy0-561-2

Graph -7x-6y=5